STEM-Gender Stereotypes: Associations With School Empowerment and School Engagement Among Italian and Nigerian Adolescents - Musso, Pasquale; Ligorio, Maria Beatrice; Ibe, Ebere; Annese, Susanna; Semeraro, Cristina; Cassibba, Rosalinda (Frontiers in Psychology, 2022)
While many sociocultural, contextual, biological, behavioral, and psychological variables may contribute to the widespread under-representation of girls and women in science, technology, engineering, and mathematics (STEM) field, the current study focused on STEM-gender stereotypes, school experiences, and adolescence as critical factors in driving students’ interest and motivation in STEM. Based on this, the current study (a) investigated differences by gender and national context (Italy vs. Nigeria) in adolescents’ STEM-gender stereotypes, school empowerment, and school engagement in a preliminary step, and (b) simultaneously examined how adolescents’ STEM-gender stereotypes related to school empowerment and school engagement as well as to socio-economic status (SES). These latter relations were considered within the context of the potential moderating role of gender and national context. Participants included 213 Italian adolescents (Mage = 13.91; 52.1% girls) and 214 Nigerian adolescents (Mage = 13.92; 60.3% girls), who completed measures of school empowerment and engagement, STEM-gender stereotypes, and SES. A multivariate analysis of covariance showed that Nigerian girls and boys reported significantly higher levels of school empowerment, school engagement, and STEM-gender stereotypes than Italian peers. Moreover, regardless the national context, boys scored significantly higher on school empowerment and STEM-gender stereotypes than girls. Furthermore, a multiple-group path analysis revealed how higher school empowerment was related to lower STEM-gender stereotypes in both Italian and Nigerian girls’ groups, while higher school engagement was associated with lower STEM-gender stereotypes only in the Nigerian groups. Regardless of gender and nationality, higher SES was linked to lower STEM-gender stereotypes. These findings particularly suggest that school empowerment and school engagement can be relevant dimensions to be studied and to develop strategies to counteract STEM-gender stereotypes in adolescence. Nonetheless, gender and national context are key factors to be considered. Limitations, strengths, future research, and educational implications are discussed.